Human-forest interaction in Aborlan Guba System, Palawan Island, Philippines implications for conservation and management - Sopsop, Lita B. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2011)
The dynamics of human-forest interaction in Aborlan Guba System, Aborlan, Palawan was determined by doing social and literature surveys and by using the STELLA program for model development. The direct users of the forest were poor indigenous peoples and migrants. Income, family size, education and size of cultivated farm significantly influenced the harvest frequency of forest products. Using current data and trends to extrapolate conditions over the next 50 years, the simulation showed that the Aborlan Guba System would become less and less sustainable in ecological and socioeconomic terms. The model projected that forest cover declines at 3 ha/year. The best way to sustainably manage the Aborlan Guba System is by increasing people's income, reducing population growth and increasing reforestation efforts especially for rattan species and almaciga trees. For immediate protection, the area must be upgraded from a controlled use zone to core zone but declaring it into a protected area under NIPAS law ensures its long term sustainability.